Doubly Switchable Diastereodivergent Strategy Mediated by a Chiral Sulfoxide to Access Disubstituted Tetrahydrocyclopentapyranone and Hexahydrocyclopentapyranol Scaffolds via Nazarov Cyclization - Grenet, Erwann; van der Lee, Arie; Salom-Roig, Xavier J. (Synthesis, 2022)
Activated dienones bearing a chiral sulfoxide were transformed diastereodivergently into the corresponding disubstituted 3,4,5,6-tetrahydrocyclopenta[b]pyran-7(2H)-ones. The torquoselectivity of the reaction could be switched by changing the Lewis acid used as promoter. From the four possible stereoisomers, only the two trans were observed. In a second switchable diastereodivergent step, both corresponding diastereomeric 2,3,4,5,6,7-hexahydrocyclopenta[b]pyran-7-ols were obtained via the diastereoselective reduction of the ketone by changing the reducing agent. The Lewis acids as well as the reducing agents employed in both diastereodivergent steps were achiral, the diastereoselectivities being dictated by the sulfinyl auxiliary.
Keywords: asymmetric synthesis; chiral auxiliaries; cyclization; diastereoselectivity; stereoselective synthesis